2005
DOI: 10.1111/j.1365-3040.2005.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered polar and lateral auxin transport in the gravity persistent signal (gps) mutants of Arabidopsis

Abstract: Plant shoots do not respond when they are reoriented relative to gravity at 4 °°°° C. However, when returned to vertical at room temperature, these organs bend in response to the previous cold gravistimulation. The inflorescence stem of the Arabidopsis thaliana gravity persistent signal (gps) mutants respond abnormally after the cold gravistimulation: gps 1 does not bend when returned to room temperature, gps 2 bends the wrong way and gps 3 over-responds, curving past the predicted angle. In wild type and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…However, comparatively little insight has been gained so far about the response of this hormone under temperature stress. Previous studies have shown that high temperature alters the plant's auxin response by altering its biosynthesis , whereas cold temperature affects the polar and lateral transport of auxin (Morris, 1979;Wyatt et al, 2002;Nadella et al, 2006). Although these studies demonstrate a link between auxin and temperature stress, the molecular and cellular mechanisms that regulate the auxin response under temperature stress, particularly for cold, remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, comparatively little insight has been gained so far about the response of this hormone under temperature stress. Previous studies have shown that high temperature alters the plant's auxin response by altering its biosynthesis , whereas cold temperature affects the polar and lateral transport of auxin (Morris, 1979;Wyatt et al, 2002;Nadella et al, 2006). Although these studies demonstrate a link between auxin and temperature stress, the molecular and cellular mechanisms that regulate the auxin response under temperature stress, particularly for cold, remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the existence of a gravity-persistent signal and indicates that cold stress acts after gravity perception (Fukaki et al, 1996;Wyatt et al, 2002). Furthermore, basipetal auxin transport in the inflorescence was abolished at 48C but was restored to the wild-type level soon after the plant was returned to room temperature (Wyatt et al, 2002;Nadella et al, 2006). To identify components that separate the perception events from the response, Wyatt et al (2002) screened for mutants in which the gravity-persistent signal was aberrant.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…4,29 Other puzzling data also fall in the right place. For instance, the rapid blockage of PAT after cold exposure, 56,57 which is also known to block endocytosis in root cells, 16 and almost immediate recovery of PAT after returning the plants to room temperature. 56,57 For example, the finding that synaptic proteins occur in plants, like the Arabidopsis protein BIG which is present in plant and animal genomes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the rapid blockage of PAT after cold exposure, 56,57 which is also known to block endocytosis in root cells, 16 and almost immediate recovery of PAT after returning the plants to room temperature. 56,57 For example, the finding that synaptic proteins occur in plants, like the Arabidopsis protein BIG which is present in plant and animal genomes. This protein, which has similarity to the synaptic protein CALLOSIN/ PUSHOVER driving synaptic signal transmission at neuromuscular synapses, is essential for PAT in plants 12,58 and its action is related to endocytosis and vesicle recycling at plant end-poles acting as plant synapses.…”
Section: Discussionmentioning
confidence: 99%